Use of spyware integrated with prediction models for computer monitoring - Noetzold, D.; Rossetto, A.; Izquierdo, L.; Valderi Leithardt (2023 18th Iberian Conference on Information Systems and Technologies (CISTI), 2023)
he new scenario of technological innovations and expansion of Internet access have created the need for greater monitoring in the workplace in order to control inappropriate behavior or situations that may cause misfortune. Two important problems faced are the dissemination of hate speech through networks and data leaks that can have social, psychological, and financial impacts. Therefore, monitoring tools can be incorporated to assist in surveillance and thus ensure the achievement of organizational goals. This work presents a computer monitoring solution in the workplace that integrates spyware techniques, sentiment classification in texts, along with a distributed architecture in microservices, aimed at collecting a series of information and generating alerts to managers regarding hate speech and vulnerabilities. Preliminary tests were conducted to evaluate the performance of the Spyware integrated with prediction models.